PENGARUH HYPNOBIRTHING TERHADAP LAMA PERSALINAN KALA II PADA IBU BERSALIN PRIMIGRAVIDA - Desy Syswianti; Tri Wahyuni; Dina Mardiana (JKM (Jurnal Kebidanan Malahayati), 2020)
ABSTRACT Background: The labor process does not run smoothly if it is not handled properly. Hypnobirthing is an alternative to speed up the labor process. This technique aims to make the mother have a calm spirit with positive energy, which helps relieve pain and anxiety during contractions which have an impact on weakening the uterine contractions and causing the labor process to take a long time. Hypnobirthing can eliminate fear of women during childbirth so that the uterine muscles relax. This will make labor easier and lead to a stress-free delivery.Purposes: To find out the comparison of the length of the second stage of labor in mothers who apply hypnobirthing and do not apply hypnobirthing, as well as to analyze the effect of hypnobirthing on the duration of the second stage of labor at the Midwife Practice Dina Garut.Methods: This research is a quasy experiment, with posttest only with control group design. The research was conducted at the Practical Midwife Dina Garut. The sample was selected by purposive sampling, as many as 20 pregnant women for each sample group. Data collection was carried out by observation using the observation sheet for the duration of second stage labor. The data analysis used was the independent sample t test.Results: The results showed that the average of second stage lenght of labor in the experimental group was 20.24 minutes and the standard deviation was 3.0758. The average of second stage lenght of labor in the control group was 20 - 45 minutes and the standard deviation was 7.3045. Independent sample t test results obtained t of -8.746 and p of 0.000 (p <0.05), so hypnobirthing affects the length of second stage of labor. Conclusion: Hypnobirthing influences the length of second stage of labor in primigravida mothers at BPM Midwife Dina Garut.Suggestion: BPM Dina in particular and in general all midwives in the Garut area, in order to be able to apply to all pregnant women regarding hypnobirthing at an affordable cost, and apply to the entire delivery process Keywords: Hypnobirthing, the length of second stage of labor ABSTRAK Latar Belakang: Proses persalinan tidak berjalan lancar jika tidak ditangani dengan benar. Hypnobirthing menjadi alternatif untuk mempercepat proses persalinan. Teknik ini bertujuan agar ibu memiliki jiwa yang tenang dengan energi positif, yang membantu menghilangkan rasa sakit dan kecemasan selama kontraksi yang berdampak pada melemahnya kontraksi rahim dan menyebabkan proses persalinan berjalan lama.  Hypnobirthing dapat menghilangkan rasa takut pada wanita saat melahirkan sehingga otot rahim menjadi relaksasi. Hal ini akan mempermudah proses persalinan dan menyebabkan persalinan yang bebas stres.Tujuan: Untuk mengetahui perbandingan lama persalinan kala II pada ibu yang menerapkan hypnobirthing dan tidak menerapkan hypnobirthing, serta menganalisis pengaruh hypnobirthing terhadap lama persalinan kala II di Bidan Praktik  Dina Garut.Metode: Penelitian ini merupakan quasy eksperimen, dengan posttest only with control group design. Penelitian dilakukan di Bidan Praktik Dina Garut. Sampel dipilih dengan purposive sampling, sebanyak 20 wanita hamil untuk setiap kelompok sampel. Pengumpulan data dilakukan secara observasi dengan menggunakan lembar observasi lama persalinan kala II. Analisis data yang digunakan adalah uji t sampel independen.Hasil: Hasil penelitian menunjukkan bahwa rata-rata lama persalinan kala II pada kelompok eksperimen adalah 20,24 menit dan standar deviasi adalah 3,0758. Rata-rata lama persalinan kala II pada kelompok kontrol adalah 20 - 45 menit dan standar deviasi adalah 7,3045. Hasil uji t sampel independen diperoleh t sebesar -8,746 dan p sebesar 0,000 (p <0,05), sehingga hypnobirthing berpengaruh terhadap lama persalinan kala II.Kesimpulan: Hypnobirthing berpengaruh terhadap lama persalinan kala II pada ibu primigravida di BPM Bidan Dina Garut.Saran Bidan Praktik Dina khususnya dan secara umum seluruh bidan yang ada di wilayah Garut, agar dapat menerapkan kepada seluruh ibu hamil mengenai hypnobirthing dengan biaya yang terjangkau, dan menerapkan pada seluruh proses persalinan Kata Kunci: Hypnobirthing, Lama Persalinan Kala II